Uwarunkowania aktywności zawodowej osób z ograniczeniami sprawności: kapitał osobisty i społeczny - Brzezińska, Anna Izabela; Kaczan, Radosław; Piotrowski, Konrad; Rycielski, Piotr (My University, 2008)
The following article is the second in a series (see „Nauka” 1/2008) presenting the results concerning the relationship between personal and social capital and level of life satisfaction among disabled people engaged in various professions. Personal capital is constructed on the basis of early socialization experiences within the family such as: number of responsibilities set by parents, degree of freedom, independent decision making, and parent-child relations. Social capital includes: respondent’s level of education (measured by years of studies), parent’s education, number of acquaintances, number of disabled people among acquaintances, family’s reaction to respondent’s needs and problems, and respondent’s perception of family support. Personal capital is an important predictor of life satisfaction among three subject groups – those engaged in employment activities (employed, formerly employed and searching for work, presently unemployed and not searching for work). Family support was isolated as an important predictor of life satisfaction among all five groups designated by professional status.
Factors influencing disabled people’s professional activity: personal and social capital
W artykule prezentujemy wybrane wyniki badań, dotyczące uwarunkowań satysfakcji z życia u pięciu grup osób niepełnosprawnych różniących się w chwili badania statusem zawodowym. Uwarunkowania te podzieliliśmy na dwie grupy. Pierwsza to zasoby indywidualne zgromadzone w okresie dzieciństwa, określamy je mianem kapitału osobistego. Druga grupa to kapitał społeczny, czyli to wszystko, co jednostka posiada w związku i dzięki kontaktom społecznym z innymi ludźmi.(...)Wyniki, które prezentujemy i poddajemy analizie, pochodzą z badań przeprowadzonych w lipcu 2007 roku przez firmę PENTOR Research International SA na terenie całej Polski na populacji osób niepełnosprawnych prawnie – aktywnych i biernych zawodowo o umiarkowanym i znacznym stopniu niepełnosprawności w wieku 18-60/65 lat. Zrealizowanych zostało 1498 wywiadów. Przy doborze próby stosowano następujące kryteria: (1) kryteria lokalizacyjne (województwo i miejsce zamieszkania – wieś/miasto), (2) kryteria demograficzne: płeć i wiek (grupa w wieku 18-29 lat, w wieku 30-49 lat oraz grupa powyżej 50 lat; (3) kryteria związane z niepełnosprawnością: stopień niepełnosprawności (umiarkowany i znaczny) oraz rodzaj niepełnosprawności (niepełnosprawność słuchowa, ruchowa, wzrokowa, psychiczna, somatyczna).
Keywords: Handicapped persons; Personal capital; Social capital; Vocational status; Life satisfaction